FINANCIAL KNOWLEDGE, ATTITUDES, AND CULTURE AS DETERMINANTS OF FINANCIAL LITERACY: THE MEDIATING ROLE OF FINANCIAL BEHAVIOR AMONG GENERATION Z - Anindia Frisna; Naelati Tubastuvi; Fatmah Bagis; Maulida Nurul Innayah (SEGMEN: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of financial knowledge, financial attitude, and financial culture on financial literacy, with financial behavior as a mediating variable among Generation Z in Banyumas Regency. The research addresses the problem of how financial behavior strengthens the role of individual financial factors in improving financial literacy among young generations.This study employs a quantitative approach using purposive sampling with 245 respondents aged 13–28 years. Data were collected through a Likert-scale questionnaire (1–5) and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that financial knowledge, financial attitude, and financial culture have a positive and significant effect on financial behavior. Financial knowledge and financial culture also have a direct positive and significant effect on financial literacy, while financial attitude does not show a significant direct effect. Furthermore, financial behavior positively and significantly mediates the relationship between financial knowledge, financial attitude, and financial culture on financial literacy